Impact of the great recession on self-perceived health in Spain: a longitudinal study with individual data - Saez, M; Vidiella-Martin, J; Casasnovas, GL (BMJ Publishing Group, 2019)
Objectives Our objective in this study is to evaluate the impact the Great Recession (2008–2014) had on self-perceived health in Spain.